Bamboo-reinforced glulam beams: an alternative to fiberglass-reinforced glulam beams (2012)
A research study was undertaken to investigate the mechanical performance of glulam beams reinforced by fiberglass fabrics or bamboo. Local reinforcement is proposed in order to improve the flexural strength and ductility of glulam beams. The glulam beam is strengthened in tension and along its sides with the fiberglass or bamboo. A series of fiberglass-reinforced glulam beams and bamboo-reinforced glulam beams were tested to determine their load-deformation characteristics. Experimental work for evaluating the reinforcing technique is reported here. According to experiment results, the fiberglass and bamboo reinforcements led to a higher glulam beam performance. The results show a considerably improved stiffness of the reinforced over the non-reinforced specimens. By using fibreglass and bamboo reinforcements, several improvements in strength and stiffness may be obtained.